Analysis Of Factors Causing Variations In Asphalt Penetration Test Results Among Civil Engineering Students In Highway Engineering Laboratory Practicum - Kadek Adi Mahendra (Journal of Advanced Engineering and Technology Research, 2026)
Variations in asphalt penetration test results are a recurring phenomenon in highway engineering laboratory practicums, particularly when tests are conducted by students with differing levels of technical skills and procedural understanding. These variations may compromise the reliability and consistency of laboratory outcomes if not properly analyzed. This study aims to identify and analyze the factors contributing to variations in asphalt penetration test results performed by civil engineering students during highway laboratory practicums. The research employed a quantitative descriptive approach using a survey method. The population consisted of 150 fifth-semester civil engineering students from the 2023 cohort at the University of Lampung, with a sample of 60 respondents selected through simple random sampling. Data were collected using a structured questionnaire based on validated indicators, including compliance with standard operating procedures, time control, temperature control, instrument reading accuracy, needle positioning, and students’ practical experience. Descriptive statistical analysis was applied to evaluate the tendency and distribution of responses. The results indicate that temperature control, time consistency, and instrument reading accuracy are the dominant factors influencing test result variations. The study recommends strengthening procedural supervision, improving laboratory instruction clarity, and integrating simulation-based practicum learning to enhance students’ technical competence and reduce testing variability